Detection of Novel SARS-like and Other Coronaviruses in Bats from Kenya - Tong, Suxiang; Conrardy, Christina; Ruone, Susan; Kuzmin, Ivan V.; Guo, Xiling; Tao, Ying; Niezgoda, Michael; Haynes, Lia; Agwanda, Bernard; Breiman, Robert F.; Anderson, Larry J.; Rupprecht, Charles E. (Emerging infectious diseases, 2009)
Diverse coronaviruses have been identified in bats from several continents but not from Africa. We identified group 1 and 2 coronaviruses in bats in Kenya, including SARS-related coronaviruses. The sequence diversity suggests that bats are well-established reservoirs for and likely sources of coronaviruses for many species, including humans.